BRIGADE THOLIBAN: POLITIK LOKAL SANTRI ANTARA KEPENTINGAN DAKWAH DAN TUNTUTAN EKONOMI - Acep Aripudin (Millah: Journal of Religious Studies, 2013)
This article proves that social movements based on religious ideology of Islam is especially dynamic follow context socio-historical developments that occur. Response of Islamic leaders on moral concerns that plagued his people become the main base that considers the importance of taking action as propaganda. Pure propaganda movement religious movement has implicitly foothold in Islam. The moral movement later developed into a political movement with a target of obtaining the rights to get the role and influence in society. Formalization of Sharia law into the legal foundation of public life in Tasikmalaya district and is an important target Tholiban movement supported other Islamic organizations are congenial with Tholiban.